A possible case of tuberculosis from a medieval site in northeast Italy. The infant of the Immacolata and San Zenone church, Tassullo, Trentino - Larentis, Omar; Tonina, Enrica (Medicina Historica, 2021)
We present a possible case of tuberculosis found in an infant from the Immacolata and San Zenone church. The cemetery was investigated/found during the 2003-2006 archaeological campaigns in the main nave of the church. In particular, we focus our attention on SU 21 c, a 9 months subject that shows pathological evidence on both the skull and the thorax. In the endocranium, we found evidence of Serpens Endocrania Symmetrica (SES) and marked porosity, and on the ribs, we detected new bone tissue apposition on the ventral surface. The subject presented here contributes to the literature related to the prevalence of tuberculosis in Italy during the last centuries in north Italy.